ANALISIS FINANCIAL LEVERAGE, GROWTH, DAN RISIKO BISNIS TERHADAP PROFITABILITAS PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 PADA PERIODE 2013-2017 - Aglen, Lorraine Analia; Panjaitan, Yunia (Jurnal Manajemen, 2019)
This study aims to examine the effect of financial leverage, growth, and business risk on firm’s profitability. Using 18 companies listed on LQ45 index during 2013 – 2017. The research used a panel data regression analysis method with Fixed Effect Model (FEM) as the estimator model. The findings suggest that financial leverage has a negative effect on firm’s profitability, asset growth has a positive effect on firm’s profitability, and business risk does not affect firm’s profitability.